DEVELOPMENT OF FARM ADVISORY SERVICE IN UZBEKISTAN IN FRAMEWORK OF RATES PROJECT - S. S. Gulomov; S. A. Adilov; S. Iskulov (Journal Park Publishing, 2025)
For Uzbek farmers to thrive and transform, access to extension services is essential. Extension services that enable farmers to overcome barriers to improve their productivity, manage their farms as sustainable businesses, connect to input and product markets, and act collectively to improve their livelihoods are the first line of action to increase rural growth in the country. Improving advisory services in Uzbekistan is a vital part of the country's development agenda, as reflected in the Agri-Food Sector Development Strategy (2020-2030). The strategy recognizes the importance of improving public sector services, opening up new markets for farmers and agribusinesses and introducing new technologies to the sector. In this endeavor, the RATEC project can play a decisive role, contributing directly to the achievement of many of the 2030 goals. However, ensuring equal access to extension services for Uzbek farmers remains a challenge that the government must address to improve the situation in rural livelihoods and overcome rural poverty in the country. To address this challenge, we tried to answer the following questions during the second year of the project: What are the local realities and challenges faced by farmers? What services do farmers need to overcome these constraints and gain better livelihood opportunities? What type of advisory and training support is available and how effective are they in reaching farmers and agribusinesses? What gaps exist in service support and how can the private and public sectors and other actors work together to fill them? These questions formed the basis for the second year of the RATEC project in the Tashkent region as part of the methodology for identifying advisory positions needed at the district advisory level. As part of the project, capacity-building trainings were organized for extension specialists and farmers in the Tashkent region, which includes 18 districts. Capacity building training for extension workers focused on improving agricultural practices.